Open and closed door moisture transport and corresponding energy consumption in household refrigerator - Saidur, Rahman; Sattar, M.A.; Hasanuzzaman, M.; Cheng, C.F.; Masjuki, Haji Hassan (Journal of Energy & Environment, 2007)
This paper presents the mode of moisture transport and their effect on energy consumption during open and closed door condition. Moisture can be transported into the refrigerator during closed and opening door conditions. Open door moisture transport depends on the number of door opening and duration of door remains open. The rate of moisture transport during open and closed door condition and energy consumption are calculated. The result of this study shows that the refrigerator with door openings consumes 8 more energy than the same refrigerator without door openings. The extra power consumption due to moisture transport during the period of 10 year by the refrigerators in Malaysia is calculated and found that 4 of the total energy is consumed.